Thrombosis and thrombocytopenia after HPV vaccination. (7th December 2021) - Johansen, Silje; Lægreid, Ingvild Jenssen; Ernstsen, Siw Leiknes; Azrakhsh, Nessar Ahmad; Kittang, Astrid Olsnes; Lindås, Roald; Gjertsen, Bjørn Tore; Vetti, Nils; Mørtberg, Trude Victoria; Sørvoll, Ingvild Hausberg; Holme, Pål André; Ahlen, Maria Therese; et al.
Abstract: Background: Vaccine‐induced immune thrombotic thrombocytopenia (VITT) has so far only been reported after adenovirus vector severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) vaccines. Objective: We report findings in a 25‐year‐old woman who presented with thrombocytopenia, venous thrombosis, elevated D‐dimer levels, and high levels of platelet‐activating antibodies to platelet factor 4‐polyanion complexes 10 days after Gardasil 9 vaccination for human papillomavirus (HPV). The patient exhibited clinical and laboratory features in line with the recently defined VITT syndrome, described after adenoviral vector vaccination to prevent coronavirus disease 2019. Conclusion: We report a case of VITT following HPV vaccination. This should raise awareness of the possibility of VITT also occurring after other vaccines, not exclusively adenoviral vector‐based SARS‐CoV‐2 vaccines.